Correlations of Job Burnout and Selected Features of Work Environment in a Sample of Midwives who Assist at Medical Abortions - Jolanta Banasiewicz; Hanna Rozenek; Stanisław Wójtowicz; Witold Pawłowski (Kazimierz Wielki University, 2017)
Background: Medical abortions have been carried out in Poland for years, and assisting at such procedures is one of professional duties of midwives who work in some Obstetrics & Gynecology Clinics. To investigate what kind of professional and psychological consequences midwives can experience in result of assisting at medical abortions, and to explore correlations between professional burnout and selected features of work environment in this population. Materials and methods: The study sample, which consisted of181 midwives working in Mazovian and Lublin Voivodeships in Poland, included 94 individuals (51.9%) who had been assisting at medical abortions and 87 individuals (48.1) who had not. The research data were collected by means of the following questionnaires: Job Control subscale of the PWP, Perceived Social Support and Current Social Support subscales of the BSSS, the OLBI, and a questionnaire created by the researchers in order to gather participants' demographic data and professional history. Results:Low perceived control at work and low social support from coworkers and supervisors are correlated with professional burnout in this population. Assisting at eugenic abortion procedures is correlated with the highest number of negative consequences. High social support and high perceived control at work are correlated with lower professional burnout.